Contribution à l’étude de l’effet de la bentonite sur la séquestration du carbone organique du sol sous climat semi-aride - MERZOUGUI, Fatma (My University, 2025)
The organic carbon storage in the soil (SCOS) is an important element in international efforts to combat climate change, as it helps reduce greenhouse gas emissions. Soil acts as a natural carbon reservoir. Since the soils of the wilaya of Mostaganem have a sandy texture in their sets and poor in organic matter, therefore provided with a high permeability which induces a leaching of fine elements, for this reason, it was thought to make amendments (i) organic (manure), (ii) mineral (bentonite: raw clay) and (iii) in the form of a mixture (manure + bentonite) with appropriate doses to improve soil physical and chemical fertility namely: bulk density, storage of organic carbon in the soil, the nutrient content of nitrogen, phosphorus and potassium and the C:N ratio. To do this, we chose the following doses: 2.5%, 5%, 7.5%, 10%, 15% and 20%. Therefore the dose of 20% manure gave the best result for all parameters but also the bentonite alone and the combination of treatments gave remarkable results in comparison with the control soil. These results highlight the role of manure in soil fertility and the combination of mineral and organic amendments in stabilizing the structure and improving the soil specially with the AF 20% treatment, Organic soil amendments increase the content of organic matter and mineral amendments protect it from the mineralizing activity of microorganisms and enrich the soil with nutrients and long-term organic carbon.
Keywords: Organic carbon sequestration; Bentonite; Manure; Mostaganem; Sandy soils; Fertility; Semi-arid climate